1995
DOI: 10.1055/s-0038-1649925
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Protein S, Protein C, and Factor X: Effects of Sex, Hormonal State and Age

Abstract: SummaryWe measured total and free protein S (PS), protein C (PC) and factor X (FX) in 393 healthy blood donors to assess differences in relation to sex, hormonal state and age. All measured proteins were lower in women as compared to men, as were levels in premenopausal women as compared to postmenopausal women. Multiple regression analysis showed that both age and subgroup (men, pre- and postmenopausal women) were of significance for the levels of total and free PS and PC, the subgroup effect being caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
34
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 13 publications
9
34
0
1
Order By: Relevance
“…Age-and sex-related tendencies were found to be similar in the Chinese population and three other populations from Scotland, 28 Italy 27 and Japan. 20 These four studies and a number of other reports 26,[45][46] were concordant in showing that PS levels were lower in women than in men, with the values being lowest before the age of 45 years, 50 as in our study. Interestingly, the findings of the Japanese studies were most closely similar to those in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Age-and sex-related tendencies were found to be similar in the Chinese population and three other populations from Scotland, 28 Italy 27 and Japan. 20 These four studies and a number of other reports 26,[45][46] were concordant in showing that PS levels were lower in women than in men, with the values being lowest before the age of 45 years, 50 as in our study. Interestingly, the findings of the Japanese studies were most closely similar to those in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The differences in protein activities between men and women, especially for PS, might indicate a role of sex hormones, most likely estrogens, in the regulation of anticoagulant factors levels under physiological conditions, as already reported, 45,46 although other mechanisms have been proposed. Falkon et al 47 found no relationship between estradiol levels and total or free PS concentration and suggested that low PS levels in young women might result from a combined effect of diverse stimuli on PS synthesis and/or metabolism.…”
Section: Discussionmentioning
confidence: 58%
“…25 we also estimated the effect of obesity on protein S levels. Mean differences were adjusted for age and gender, as both age and gender influence protein S levels, 26 and for each other in a multivariate analysis. Because there is no reason to assume that low levels of protein S are more common among partners of patients than in the general population, both RDD subjects and partners of patients were considered as control subjects and all analyses were unmatched.…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental and inherited factors condition PS plasma levels, including lipid profile, variables associated with insulin resistance, oral contraceptive pills or hormone replacement therapy, sex, age and body mass index (BMI) [1][2][3][4]. Normally, approximately 30-40% of PS circulates freely in plasma and 60-70% is bound to C4b-binding protein (C4Bbp).…”
mentioning
confidence: 99%
“…The PZdependent protease inhibitor in the presence of PZ causes fast inactivation of factor Xa. Recently, reduced circulating levels of PZ have been suggested to play a role in the occurrence of bleeding [2] and deep vein thrombosis [3,4], as well as primary aborts with unexplained early fetal loss [5]. However, these data have been disputed [6][7][8].…”
mentioning
confidence: 99%